2011
DOI: 10.4028/www.scientific.net/msf.679-680.386
|View full text |Cite
|
Sign up to set email alerts
|

Energy Band Structure of SiO<sub>2</sub>/4H-SiC Interfaces and its Modulation Induced by Intrinsic and Extrinsic Interface Charge Transfer

Abstract: The energy band structure of SiO2/4H-SiC fabricated on (0001) Si- and (000-1) C-face substrates was investigated by means of synchrotron radiation x-ray photoelectron spectroscopy (SR-XPS). The band structure was found to be dependent on substrate orientation and oxide thickness due to both intrinsic and extrinsic effects that cause charge transfer at the SiO2/SiC interface. Our SR-XPS analysis revealed that the intrinsic conduction band offset of the SiO2/SiC for the C-face substrate is smaller than that for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 7 publications
3
22
0
Order By: Relevance
“…As shown in Fig. 7, O 1s energy loss spectra for thermal oxides on the Si-face and C-face substrates clearly indicate that the energy band gap of the oxides is identical regardless of substrate orientation (8.7 eV) [24]. Considering the high oxidation temperatures over 1000˚C and low concentration of residual carbon impurities within thermally grown oxides on SiC [17], these results seem to be quite reasonable.…”
Section: Energy Band Structure Of Sio 2 /4h-sic Interfaces and Its Mosupporting
confidence: 53%
See 1 more Smart Citation
“…As shown in Fig. 7, O 1s energy loss spectra for thermal oxides on the Si-face and C-face substrates clearly indicate that the energy band gap of the oxides is identical regardless of substrate orientation (8.7 eV) [24]. Considering the high oxidation temperatures over 1000˚C and low concentration of residual carbon impurities within thermally grown oxides on SiC [17], these results seem to be quite reasonable.…”
Section: Energy Band Structure Of Sio 2 /4h-sic Interfaces and Its Mosupporting
confidence: 53%
“…O 1s energy loss spectra for thermal oxides on (0001) Si-face and (000-1) C-face 4H-SiC substrates. The onset of the excitation from the valence to conduction bands (band gap) can be determined from the energy loss.The valence band maximum of SiC substrates and the oxides was determined by the valence spectra taken from SiO 2 /SiC structures and a reference SiC surface [24]. Figure 8 represents measured and deconvoluted valence spectra obtained after 3-nm oxidation of the Si-face and C-face substrates, in which the valence band maximum of the thermal oxides was estimated by subtracting the reference SiC spectra (②) from the measured SiO 2 /SiC spectra (②) both for the Si-and C-face substrates (see…”
Section: Correlation Between Atomic Structure and Electrical Propertimentioning
confidence: 99%
“…The energy band structure was examined by observing energy loss spectra for O1s photoelectron and valence band spectra for oxides grown on SiC substrates (23). Figure 5 shows Si 2p 3/2 photoelectron spectra taken from the thin-SiO 2 /4H-SiC structures grown on Si-and C-face substrates (24). The binding energy position was calibrated by the SiC bulk signal, as indicated by the dotted line.…”
Section: Energy Band Structure Of Sio 2 /4h-sic Interfaces and Its Momentioning
confidence: 99%
“…This phenomenon is sensitive to the local structure at the interface. Indeed, it has been reported that the shift in the band alignment of SiC and oxide can be induced by performing hydrogen annealing after the gate oxidation [39,40]. Based on these observations, we propose the hypothesis that the small defects at the interface cause a rearrangement of the charge transfer layer, which leads to the formation of a large dipole.…”
mentioning
confidence: 67%